That all shall be saved: heaven, hell, and universal salvation - Hart, David Bentley (Yale University Press, 2019)
Cover -- Half Title -- Title -- Copyright -- Dedication -- Contents -- Introduction -- PART I: THE QUESTION OF AN ETERNAL HELL -- Framing the Question -- Doubting the Answers -- PART II: APOKATASTASIS: FOUR MEDITATIONS -- First Meditation: Who Is God? The Moral Meaning of Creatio ex Nihilo -- Second Meditation: What Is Judgment? A Reflection on Biblical Eschatology -- Third Meditation: What Is a Person? A Reflection on the Divine Image -- Fourth Meditation: What Is Freedom? A Reflection on the Rational Will -- PART III: WHAT MAY BE BELIEVED -- Final Remarks -- Acknowledgments and Bibliographical Notes -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- U -- V -- W -- X -- Z.